The use of associated gas in a petroleum exporting country: An optimal control model - Michael Rauscher (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1985)
Currently, the world petroleum market is facing attempts by petroleum exporting countries to extend their influence further downstream. The process of vertical integration is based on natural gas which accrues as a by-product of crude oil recovery. Gas can be used for downstream production, for reinjection into the oil field in order to enhance future recovery, or it can simply be flared. The model investigates how to optimally use the associated gas in an inter temporal framework. The price and extraction paths, associated with the optimal use of gas are examined, compared with the relevant time paths of the standard model.
Keywords: 330